Ocupações do cotidiano de usuários/as do Centro de Convivência em Saúde Mental na Pandemia de Covid-19 - Heldevam Pereira Campos Junior (2022)
The Covid-19 Pandemic and its resulting protective measures have been identified as a source of occupational disruption in the daily lives of people in different contexts. The aim of this study was to investigate how the occupations in users’ everyday lives the repercussions of the Pandemics on occupations performed in the daily lives of users of a Conviviality Center, a service part of the Brazilian Psychosocial Care Network. For that, a qualitative research was carried out, in the format of a case study through semi-structured interviews, accompanied by a field diary, with 14 users, 11 men and 3 women, mostly black people from low income. From the Content Analysis, two categories emerged: (1) occupations performed in the Conviviality Center and (2) occupations performed in their houses. It was identified that the participants already had a life almost entirely restricted to their homes in a moment before the Pandemic, with limited social circulation and opportunities for leisure and work, with the Conviviality Center often being one of the only frequented places. In the service, participants experienced a reduction in weekly attendance and in the workshops available, in addition to changes in the ways of participating in them. At home, their routines suffered few changes, and the occupations performed in this space refered mainly to domestic work. The study points out that these people, who have their sociability links curtailed, experienced, above all, occupational disruption in their occupations performed at the Conviviality Center, but in the domestic environment, what prevailed was occupational deprivation, exacerbated by the Pandemic.